2021
DOI: 10.1002/jnr.24992
|View full text |Cite
|
Sign up to set email alerts
|

Maternal‐fetal transmission of delta‐9‐tetrahydrocannabinol (THC) and its metabolites following inhalation and injection exposure during pregnancy in rats

Abstract: Cannabis use during pregnancy has increased over the past few decades, with recent data indicating that, in youth and young adults especially, up to 22% of people report using cannabis during pregnancy. Animal models provide the ability to study prenatal cannabis exposure (PCE) with control over timing and dosage; however, these studies utilize both injection and inhalation approaches. While it is known that Δ9‐tetrahydrocannabinol (THC; primary psychoactive component of cannabis) can cross the placenta, exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 118 publications
0
20
0
Order By: Relevance
“…Therefore, administration of exogenous cannabinoids, such as THC and/or cannabidiol, may disrupt the developing eCB system and impact postnatal outcomes. Indeed, a recent preclinical study in a cannabis inhalation model demonstrated that up to 30% of THC in circulating maternal blood reaches the fetal brain (Baglot et al, 2022). In sum, our findings add to the growing body of evidence suggesting that PCE, particularly during early gestation, can have detrimental effects on offspring neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, administration of exogenous cannabinoids, such as THC and/or cannabidiol, may disrupt the developing eCB system and impact postnatal outcomes. Indeed, a recent preclinical study in a cannabis inhalation model demonstrated that up to 30% of THC in circulating maternal blood reaches the fetal brain (Baglot et al, 2022). In sum, our findings add to the growing body of evidence suggesting that PCE, particularly during early gestation, can have detrimental effects on offspring neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…The precise impact of potency and patterns of maternal cannabis use on the developing fetus remains unclear. Regardless of the method of consumption, it is clear from human and preclinical studies that the major psychoactive component of cannabis, THC, crosses the placenta into fetal tissues where it has the potential to interfere with development [for review see (16) and (17)(18)(19)(20)(21)(22)(23)(24)(25)].…”
Section: Introductionmentioning
confidence: 99%
“…A validated vapour inhalation system (La Jolla Alcohol Research Inc., California, USA) was used as previously described [35, 38]. Rats were subjected to inhalation of vapour from a THC-dominant cannabis extract containing 89.7% THC, 0.3% CBD, 1.7% CBG, 1.4% CBN and 0.6% CBC (Aphria Inc., Ontario, Canada) diluted to 10% THC in polyethylene glycol vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma and hypothalami samples were run through tandem mass spectrometry (LC-MS/MS) at the University of Calgary Southern Alberta Mass Spectrometry facility to measure THC, CBD, and THC metabolite concentrations (11-OH-THC and THC-COOH), as previously described [35, 38]. In short, 250 μl thawed plasma and homogenised whole hypothalami were added to a 20:1 solution of acetonitrile and deuterated analyte standards for THC, CBD, 11-OH-THC and THC-COOH (at a known concentration of 10 ng/ml in 1:1 methanol and water; Cerilliant, Round Rock, TX, USA).…”
Section: Methodsmentioning
confidence: 99%